Non-monetary Interventions, Workforce Retention and Hospital Quality: Evidence from the English NHS - Giuseppe Moscelli; Melisa Sayli; Jo Blanden; Marco Mello; Henrique Castro-Pires; Chris Bojke (Institute of Labor Economics (IZA), 2023)
Excessive turnover can signicantly impair an organization's performance. Using high-quality administrative data and staggered dierence-in-dierences strategies, we evaluate the impact of a programme that encouraged public hospitals to increase staff retention by providing data and guidelines on how to improve the non-pecuniary aspects of nursing jobs. We find that the programme has decreased the nurse turnover rate by 4.49%, decreased exits from the public hospital sector by 5.38%, and reduced mortality within 30 days from hospital admission by 3.45%, preventing 11,400 deaths. Our results are consistent with a theoretical model in which information is provided to managers of multi-unit organizations, who trade off coordinating decisions across units and adapting them to local conditions.
Keywords: J32; J38; J45; J63; I11; C22; 330; labor supply; workforce retention; non-monetary incentives; hospital care; staggered difference-in-differences